A Survey Study Of Yuvanpidika (Acne)In The Context Of Dosha Predominance - Rohilla, Prayasha; Sevatkar, Balkrishan (International Research Journal of Ayurveda & Yoga, 2021)
A great philosopher says, "Human faces express and represent their personality and wisdom."Yuvanpidika described under the Kshudrarogas in Ayurveda text. Yuvanpidika is one of Kshudrarogas which mainly affects the skin of face. According to Ayurveda text it occurs due to imbalance of Kapha, Vata, and Rakta. It means the eruptions occur on the face of young person is called Yuvanpidika. Sometime it may appear on upper chest & back but generally it manifests on facial skin only and this might be the reason that word Mukhdushika has been used as a synonym of Yauvanpidika at many places. Acne vulgaris (henceforth acne) is the eighth most common skin disease, according to the Global Burden of Disease Study 2010, with a global prevalence (for all ages) of 9.38 percent. Acharya Vijayrakshita, commentator of Madhava Nidana had used the term Yuvana Pidika as for Mukh-Dushika for the first time.